Silicone Foley catheters impregnated with microbial indole derivatives inhibit crystalline biofilm formation by Proteus mirabilis - Amer, Mai A.; Ramadan, Mohamed A.; Attia, Ahmed S.; Wasfi, Reham (Frontiers in Cellular and Infection Microbiology, 2022)
Proteus mirabilis is a common causative agent for catheter-associated urinary tract infections (CAUTI). The crystalline biofilm formation by P. mirabilis causes catheter encrustation and blockage leading to antibiotic treatment resistance. Thus, biofilm formation inhibition on catheters becomes a promising alternative for conventional antimicrobial-based treatment that is associated with rapid resistance development. Our previous work has demonstrated the in vitro antibiofilm activity of microbial indole derivatives against clinical isolates of P. mirabilis. Accordingly, we aim to evaluate the capacity of silicone Foley catheters impregnated with these indole derivatives to resist biofilm formation by P. mirabilis both phenotypically and on the gene expression level. Silicon Foley catheter was impregnated with indole extract recovered from the supernatant of the rhizobacterium Enterobacter sp. Zch127 and the antibiofilm activity was determined against P. mirabilis (ATCC 12435) and clinical isolate P8 cultured in artificial urine. The indole extract at sub-minimum inhibitory concentration (sub-MIC=0.5X MIC) caused a reduction in biofilm formation as exhibited by a 60-70% reduction in biomass and three log10 in adhered bacteria. Results were confirmed by visualization by scanning electron microscope. Moreover, changes in the relative gene expression of the virulence genes confirmed the antibiofilm activity of the indole extract against P. mirabilis. Differential gene expression analysis showed that extract Zch127 at its sub-MIC concentration significantly down-regulated genes associated with swarming activity: umoC, flhC, flhD, flhDC, and mrpA (p < 0.001). In addition, Zch127 extract significantly down-regulated genes associated with polyamine synthesis: speB and glnA (p < 0.001), as well as the luxS gene associated with quorum sensing. Regulatory genes for capsular polysaccharide formation; rcsB and rcsD were not significantly affected by the presence of the indole derivatives. Furthermore, the impregnated catheters and the indole extract showed minimal or no cytotoxic effect against human fibroblast cell lines indicating the safety of this intervention. Thus, the indole-impregnated catheter is proposed to act as a suitable and safe strategy for reducing P. mirabilis CAUTIs.